(untitled) (Bangladesh Journal of Medical Microbiology, 2017)
The increase in antibiotic resistance coincided with the decline in production of new antibiotics. Combination antibiotic treatment is preferred in nosocomial infections caused by multidrug resistant Pseudomonas aeruginosa. In vitro synergism test by agar dilution method were used to choose the combinations which might be used in clinic. The aim of this study was to investigate the synergistic efficacy of antibiotic combinations in imipenem resistant P. aeruginosa strains. Carbapenem resistance (imipenem and meropenem) was determined by disk diffusion method. Among isolated P. aeruginosa 44.9% were cabapenem resistant. The MIC of drugs among 25 imipenem resistant isolates ranged from >_ 256 mg/L to <_ 8 mg/L for imipenem, >_ 1024 mg/L to <_ 64 mg/L for ceftriaxone, >_ 256 mg/L to <_ 8 mg/L for amikacin, >_ 16 mg/L to <_ 2 mg/L for colistin, >_ 512 mg/L to <_ 16 mg/L for piperacillin/tazobactam. Among antibiotic combinations, piperacillin /tazobactam- amikacin was most effective with 80% synergism next to which was imipenem-amikacin with 60% synergism, then imipenem-colistin with 50% synergism, imipenem-ceftriaxone with 30% synergism. Only one combination (piperacillin/tazobactum -imipenem showed 20% antagonism. All these combinations had considerable proportion of additive effect which is also desirable for these multi drug resistant isolates. Bangladesh J Med Microbiol 2015; 9 (1): 3-8